Multiomics Profiling Establishes the Polypharmacology of FDA-Approved CDK4/6 Inhibitors and the Potential for Differential Clinical Activity. Issue 8 (15th August 2019) - Hafner, Marc; Mills, Caitlin E.; Subramanian, Kartik; Chen, Chen; Chung, Mirra; Boswell, Sarah A.; Everley, Robert A.; Liu, Changchang; Walmsley, Charlotte S.; Juric, Dejan; Sorger, Peter K.
Summary: The target profiles of many drugs are established early in their development and are not systematically revisited at the time of FDA approval. Thus, it is often unclear whether therapeutics with the same nominal targets but different chemical structures are functionally equivalent. In this paper we use five different phenotypic and biochemical assays to compare approved inhibitors of cyclin-dependent kinases 4/6—collectively regarded as breakthroughs in the treatment of hormone receptor-positive breast cancer. We find that transcriptional, proteomic, and phenotypic changes induced by palbociclib, ribociclib, and abemaciclib differ significantly; abemaciclib in particular has advantageous activities partially overlapping those of alvocidib, an older polyselective CDK inhibitor. In cells and mice, abemaciclib inhibits kinases other than CDK4/6 including CDK2/cyclin A/E—implicated in resistance to CDK4/6 inhibition—and CDK1/cyclin B. The multifaceted experimental and computational approaches described here therefore uncover underappreciated differences in CDK4/6 inhibitor activities with potential importance in treating human patients. Graphical Abstract: Highlights: Three approved CDK4/6 inhibitors have significantly different target spectra Secondary targets of abemaciclib include CDK1-cyclin B and CDK2-cyclin A/E complexes Only abemaciclib induces G2 cell-cycle arrest and a pan-CDK transcriptional signature Palbociclib-resistant and -adapted cells respond to abemaciclib but not ribociclib Abstract : The CDK4/6 inhibitors, palbociclib, ribociclib, and abemaciclib are breakthrough breast cancer therapies. Using multiomics profiling, Hafner et al. show that abemaciclib alone targets additional CDKs at clinically relevant concentrations. Cell line, xenograft, and preliminary clinical data suggest that abemaciclib's polypharmacology may be therapeutically advantageous.